Locally contextualizing understandings of depression, the EPDS, and PHQ-9 among a sample of postpartum women living with HIV in Malawi - Harrington, Bryna J. (J Affect Disord, 2020)
BACKGROUND: The Edinburgh Postnatal Depression Scale (EPDS) and Patient Health Questionnaire-9 (PHQ-9) are widely used depression screening tools, yet perceptions and understandings of their questions and of depression are not well defined in cross-cultural research. METHODS: 30 postpartum women living with HIV in Malawi were recruited from a cohort study and participated in in-depth cognitive interviews. Transcripts were evaluated following an inductive approach to identify common themes. RESULTS: Participants most frequently described looking sad or different than usual, self-isolation, ‘thinking too much,’ and anger as key symptoms of being depressed. HIV-associated stigma was commonly identified as a cause of depression. The EPDS and PHQ-9 were generally well understood but did not capture all the important symptoms of depression that women described. Participants sometimes requested clarification or rephrasing of certain EPDS and PHQ-9 questions when asked to explain the questions’ meanings in their own words, and requested rephrasing more often for EPDS questions than PHQ-9 questions. Few women believed either tool was sufficient to detect depression. LIMITATIONS: Our results may not be generalizable, but are locally contextualized. Women suffering with depression may have been more or less likely to agree to the qualitative interview depending on their comfort level discussing any current depressive symptoms. CONCLUSIONS: Researchers and practitioners who use the EPDS and PHQ-9 should be aware of the tools’ limitations in their context and population. New instruments may need to be developed or adaptations to existing tools made to improve accuracy of depression screening and diagnosis in different cultural contexts.